Cooperative Learning Model Jigsaw and Interest Type in Improving Learning Outcomes of SMA Negeri 1 Sutera Kabupaten Pesisir Selatan - Resnawati Resnawati; Siti Fatimah; Buchari Nurdin (Universitas Negeri Padang, 2019)
Effect of Cooperative Model of Jigsaw Type Learning and Student Interest in improving learning outcomes in SMA Negeri 1 Sutera. The research method used in writing this essay in accordance with the type of research is quasi experimental research (quasi experimental), where the research variables can not be fully controlled. This research has a control group. The research design used to measure learning method and student's interest toward the result of dissemination of culture and religion. This research is parenting at level (2x2), with state of student interest level. The results of the study revealed (1) the learning outcomes of students who were taught by the Jigsaw cooperative model approach were better than the conventional approach, (2) the students' learning outcomes had high interests taught by the Jigsaw type cooperative model better than the conventional approach, (3) learning of students with low interests taught by Jigsaw type cooperative models is better than conventional models